HUBUNGAN KEKUATAN OTOT TUNGKAI DAN PANJANG LENGAN TERHADAP TINGGI LONCATAN (VERTICAL JUMP) PEMAIN BOLA VOLI - Yuda Natanael Bangun; Rahmad Lubis; Surya Sah Putra Ginting; Borisman Zebua; Priaman Jaya Nazara; Dewi Endriani (STKIP Subang, 2026)
This study aims to analyze the relationship between leg muscle strength and arm length on the vertical jump ability of volleyball players based on previously published research findings. The method used in this study was a literature review by examining various scientific journals, books, and other relevant academic sources. Data were collected through literature searches in academic databases and analyzed descriptively through identification, selection, classification, and synthesis of information. The results of the review indicate that leg muscle strength plays a crucial role in determining the vertical jump performance of volleyball players, as it serves as the primary source of force during take-off movements. In addition, arm length provides biomechanical advantages by increasing the player's reach during game techniques such as spiking and blocking. Based on the analysis of previous studies, it can be concluded that leg muscle strength and arm length are closely related to the vertical jump ability of volleyball players. Therefore, physical conditioning and anthropometric considerations should be important aspects in volleyball athlete development programs.